2020
DOI: 10.1101/2020.04.27.053694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein synthesis is suppressed in sporadic and familial Parkinson’s Disease by LRRK2

Abstract: Gain of function LRRK2-G2019S is the most common mutation associated with both familial and sporadic Parkinson's disease. It is expected therefore that understanding the cellular function of LRRK2 will provide much needed insight on the pathological mechanism of sporadic Parkinson's, which is the most common form. Here we show that constitutive LRRK2 activity represses nascent protein synthesis in rodent neurons. Specifically, enzymatic inhibition of LRRK2, gene silencing or gene knockout of Lrrk2 increase tra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…are described in Table 1. To label nascent proteins, cells were metabolically labeled according to the FUNCAT method as previously described 12,19 . In this procedure, endogenous methionine is replaced with the L-Azidohomoalanine (AHA) analog of methionine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…are described in Table 1. To label nascent proteins, cells were metabolically labeled according to the FUNCAT method as previously described 12,19 . In this procedure, endogenous methionine is replaced with the L-Azidohomoalanine (AHA) analog of methionine.…”
Section: Resultsmentioning
confidence: 99%
“…Isolation and LC-MS/MS identification of newly synthesized proteins from LRRK2-G2019S carriers and sporadic patients We set out to identify which mRNA transcripts were differentially regulated at the level of translation in PD patient cells, investigating both sporadic and LRRK2-G2019S cases. Skin punches were isolated from 10 sporadic PD cases and 6 healthy donors from patients attending TUH and from an accompanying family member (usually a spouse or sibling), as previously described 12 . In addition, we analyzed five fibroblast samples from LRRK-G2019S patients and six from healthy controls using material from the NINDS and TNGB repositories.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pseudo-compartmentalized translation within neural cells has been shown to create spatial variability in protein expression that is critical for neural development, function, and plasticity (34). Disruptions to localized translation have been linked to various neurodevelopmental and neurodegenerative disorders (35,36). Combined with the results linking ER/translation GO terms in these same cells, these findings indicate that dysregulation of translation and protein folding, whether at the ER and/or at distal sites, might contribute to the clinical presentation of pediatric DPD deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have suggested that LRRK2 kinase activity, even when overexpressed in cells, may be very low. Exposure of cells to oxidative stress has been reported to enhance LRRK2 activation [22,[42][43][44][45]. Since endogenous pT73-RAB10 signal in transfected HEK293T cells overexpressing LRRK2 was low (Supplementary Figure 1), we co-transfected cells with flag-tagged WT LRRK2 and GFP-tagged RAB10 (Fig.…”
Section: Lack Of Effect Of Oxidative Stress On Activity Of Overexpres...mentioning
confidence: 99%